Efeitos da ventilação mecânica não-invasiva na variabilidade da freqüência cardíaca e no padrão ventilatório de pacientes submetidos à cirurgia de revascularização do miocárdio - Pantoni, Camila Bianca Falasco (2009)
Noninvasive positive pressure ventilation (NIPPV) has been commonly applied in several clinical and postoperative conditions, especially after coronary artery bypass grafting (CABG) surgery and it can cause breathing pattern (BP) alterations and mechanical effects on cardiovascular system, with cardiac autonomic adjustments. However, it is not well established in the literature how these alterations occur in patients submitted to the CABG and if they can be related to the application of different positive airway pressure levels. In this context, we considered the development of two studies that could contribute with new information about these topics. The first study is entitled Acute application of bilevel positive airway pressure influence cardiac autonomic nervous system and its objective was to evaluate the changes in heart rate variability (HRV) during bilevel positive airway pressure (Bilevel) application in healthy young men. Twenty men underwent a 10-min register of R-R intervals (R-Ri) during sham ventilation, Bilevel 8-15cmH2O and Bilevel 13-20 cmH2O. HRV was analyzed in time and frequency-domain and with non-linear statistical measures. Physiological variables (blood pressure, breathing rate, end tidal carbon dioxide- ETCO2) were also collected. R-Ri mean, rMSSD, NN50, pNN50 and SD1 reduced during 13-20 cmH2O compared to sham ventilation, with reduction of the R-Ri mean compared to 8-15 cmH2O. R-Ri mean and high frequency band (HF) reduced and low frequency band (LF) increased during 8-15 cmH2O compared to sham ventilation. Delta of ETCO2 correlated positively with LF, HF, LF/HF, SDNN, rMSSD and SD1. In conclusion, acute application of Bilevel was able to alter cardiac autonomic nervous system, with parasympathetic activity reduction and sympathetic increase and higher level of positive airway pressure can cause a greater influence on the cardiovascular and respiratory system. The second study is entitled The effects of different levels of positive airway pressure on respiratory pattern and heart rate variability in patients submitted to coronary artery bypass grafting surgery and its objective was to access the effects of different levels of continuous positive airway pressure (CPAP) in BP and HRV in CABG postoperative (PO), as well as the impact of CABG in these variables. Eighteen patients underwent CABG was evaluated during spontaneous breathing (SB) and four different CPAP levels of CPAP, in a random order: (a) CPAP = sham (3 cmH2O), (b) 5 CPAP = cmH2O, (c) 8 CPAP= cmH2O, (d) 12 CPAP = cmH2O in PO. HRV was analysed in time and frequency domain and by non-linear methods (Poincaré plot e Detrended Fluctuation Analysis) and BP was analysed by inductive respiratory plethysmograph. There were significant alterations of HRV and BP in the PO of CRM, compared to pre-operative and alterations of DFAα1, DFAα2 e SD2 and respiratory variables during NIPPV, with higher influence observed during application of the two higher levels applied. Moreover, there was relationship between DFAα1 and inspiratory time of delta 12 cmH2O and SB, and 8 cmH2O and SB. In conclusion, acute CPAP application was able to alter the control of cardiac autonomic nervous system and BP of patients submitted to CABG and higher levels promoted better performance of pulmonary and cardiac autonomic function.